Setting aside of the distribution order made under the small estates (distribution) act 1955 on the ground of fraud; position of the law after the case of ahmad bin abd majeed v. Habibah bte abdul majid & anor - Badrol, Awang; Maheran, Makhtar (2012)
The distribution of small estates of intestate deceased persons in Malaysia is governed by the Small Estates (Distribution) Act 1955 (‘the Act’) and Small Estates (Distribution) Regulations 1955 (‘the Regulations 1955’). Under the Act, the collector shall have an exclusive jurisdiction for the distribution of small estates. The issue normally arises when a petitioner intentionally and fraudulently omits some legal beneficiaries’ names in the petition for estate distribution and the distribution order is then made based on that petition. Study shows that the applications by the excluded beneficiaries to set aside the distribution order in such cases have been consistently dismissed on the grounds that the High Court has no original jurisdiction to hear the matter and that the aggrieved party should have appealed under s 29 of the Act. The Shariah Court also has ruled that it has no jurisdiction to hear the case. The decision of the Court of Appeal in Ahmad Abd Majeed has changed the position of the law and is of a great relief for the excluded beneficiaries